PENGARUH HARGA, PROMOSI, DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN PADA PERUSAHAAN A-36 - Arief Adi Satria (Jurnal Performa)
Research aims to determine the influence of price , promotion , and product quality on consumer buying interest in a business a-36 .Population that used in this research was the consumers of business a-36 by the number of 80 respondents .Methods used in this research is regression analysis linear multiple .Research data mixed use microsoft excel and software spss 20 . Variable free of this research is the price of ( x1 ) , promotion ( x2 ) , and product quality ( x3 ) .Variable attached to this research is interest in buying (y) .This research result indicates that the price , promotion and product quality influential simultaneously of interest in buying .Variable prices , promotion and product quality also has a partial influence of the decision purchase .The variable free ( prices , promotion and product quality ) on variables bound ( interest in buying ) was in 68.9 % .Variable free that has an effect most dominant on variables bound was a factorof quality products .